Caring as a core concept in educating midwifery learners: A qualitative study - Mmajapi E. Chokwe; Susan C.D. Wright (AOSIS, 2012)
Caring is the core business of nursing and midwifery, involving a relationship in which the carer is committed to the needs of the one being cared for (Mason-Whitehead, Mcintosh, Bryan & Mason). Caring is the emotion which drives a midwife to care, the motive aimed at assisting someone to grow and self-actualise (Watson). The concern in midwifery is that irrespective of caring being central to the midwifery profession, caring taught in theoretical learning does not always translate into caring behaviour in practice. A qualitative exploratory study examined how midwifery educators impart the skill of caring during theoretical learning and clinical accompaniment, in order to respond to the general complaint made both locally and internationally that midwives are uncaring. The aim was to explore caring during theoretical learning and clinical accompaniment from the perspective of midwifery educators. Participants in the study were midwifery educators teaching midwifery in institutions of learning in Tshwane, South Africa. The naive sketch was used to gather data, wherein one central question was asked and the educators were invited to narrate and respond. Three themes emerged: the meaning of caring; how caring was conveyed during theoretical learning; and how it was conveyed during clinical accompaniment. Although the midwifery educators expressed how they conveyed caring to the learner midwives, it was not evident how caring competencies were assessed in order to ensure caring midwives at the end of training. Omgee is die kernwaarde van 'n verpleegkundige en vroedvrou. Omgee behels 'n verhouding waar die person wat omgee verbind is om in die behoeftes van die een wat sorg benodig te voldoen (Mason-Whitehead, Mcintosh, Bryan & Mason). Omgee is die emosie wat die vroedvrou noop om om te gee, om 'n person te help groei en self-aktualiseer (Watson). Die kwelpunt in verloskunde is dat ongeag van die sentrale belang van omgee vir verloskundiges, die teoretiese onderig oor omgee nie altyd uitgeleef word in die praktyk nie. 'n Kwalitatiewe ondersoekende studie het die wyse ondersoek waarop vroevrou opvoerders die vaardigheid om om te gee, oordra tydens teoretiese en kliniese begeleiding, ten einde te reageer op die plaaslike en internasionale algemene klagte, dat vroedvroue nie omgee nie. Om omgee tydens teoreties en kliniese onderrig vanuit die perspektief van die opvoedkundige verloskundige te ondersoek. Die deelnemers het bestaan uit verloskundige opvoedkundiges wat verloskunde doseer in hoёr onderwys institusies in Tshwane, Suid-Afrika. 'n Naїewe skets is gebruik om data in te samel met een sentrale vraag. Drie temas het voortgespuit: die betekenis van omgee; hoe die konsep oorgedra is tydens teoretiese onderrig; en hoe die konsep oorgedra is tydens kliniese onderrig. Alhoewel die verloskundige opvoedkundiges kon verduidelik hoe hulle omgee oorgedra het aan die leerling vroedvroue, was daar geen bewyse van hoe omgee vaardighede evalueer is nie ten einde omgee vaardige vroedvroue aan die professie te lewer.